"I have a good life": the meaning of well-being from the perspective of young adults with Down syndrome. (July 2014) - Scott, Melissa; Foley, Kitty-Rose; Bourke, Jenny; Leonard, Helen; Girdler, Sonya
Abstract Purpose: The purposes of this study were to explore what makes for a "good life" from the perspective of young adults with Down syndrome and to identify the barriers and facilitators to participation. Methods: Twelve young adults with Down syndrome participated in individual and group discussions. Each session began with individual discussions between a researcher and participant, allowing each individual to express their views in their own words. Following individual discussions, participants joined a larger group facilitated by the researchers which allowed for collective reflection and sharing of experiences. Individual discussions were recorded on large poster size pieces of paper through drawings and writing using colourful pens by the participants themselves or with assistance from researchers. Group discussions were audio recorded and one researcher recorded field notes on contextual information. Data were analyzed through open coding and constant comparison techniques to identify categories which were then collapsed into the main themes. Results: Analysis of the transcripts revealed four main themes: "Relationships", "Community participation", "Independence" and "Hopes for the future". These findings highlighted the participants' desire for autonomy, particularly in the domains of living independently and employment. Family relationships and community services were described as both facilitators and barriers to their participation. Conclusion: Overall, the findings from this study revealed that the participants' life perspective was positive, with a general consensus of, "I have a good life". This study yielded many recommendations that could be integrated into transition models of service delivery for young adults with Down syndrome as they develop from adolescence into adulthood. Implications of Rehabilitation Young people with Down syndrome want to make decisions for themselves. Community participation is important for young adults with Down syndrome. Young people with Down syndrome have dreams and aspirations for their future, and should be fully engaged in planning for transition from school.